The incidence, clinical significance of depression and its clinical course after a cardac device implantation in patients with severe heart failure. (25th November 2020) - Podolecki, T; Pudlo, R; Mazurek, M; Jedrzejczyk-Patej, E; Koziel, M; Sokal, A; Kowalski, O; Lenarczyk, R; Kalarus, Z
Abstract: Aim: To assess the incidence, clinical significance of depression and the impact of a cardioverter-defibrillator (ICD) or cardiac resynchronization therapy-defibrillator (CRT-D) implantation on psychiatric status in patients with heart failure (HF). Methods: The prospective, single-center study encompassed 575 consecutive HF patients implanted with a CRT-D or ICD. Finally, the study population consisted of 494 subjects (186 ICD and 308 CRT-D patients), as 81 patients taking antidepressants were excluded from the analysis. All patients underwent psychiatric examination at the time of implantation, and the assessment of psychiatric status was repeated after 3, 6, 12 and 24 months. The study population was divided into 4 groups: Group 1 encompassed 101 (20.4%) patients with persistent depression, Group 2 constituted of 95 (19.2%) patients with depression that developed after ICD/CRT-D implantation, whereas 43 (8.7%) patients with remission of depression comprised Group 3, and Group 4 encompassed 255 (51.6%) patients with never diagnosed depression. Data on long-term follow-up (median 34.1 months) were screened to identify patients who developed a composite endpoint defined as death or hospitalization for decompensated HF. Results: The cumulative incidence of depression at the baseline assessment was 39.1%. Depression developed in 95 (27.1%) patients, whereas remission of depression was observed in 43 (29.9%) subjects after ICD/CRT-D implantation. ICD intervention (HR 3.3) and increase in NYHA class by at least one class (HR 2.6) were the independent risk factors for depression development, whereas mitral regurgitation reduction (HR 1.9), as well as improvement in NYHA class by at least one class (HR 2.4) were the independent predictors for depression remission. Patients with persistent depression (Group 1) and those with newly developed depression (Group 2) were at significantly higher risk of a composite endpoint compared to patients in Group 3 and Group 4 (Table 1). Conclusions: Depression is a common comorbidity associated with HF, as it affects 4 of 10 HF patients. ICD intervention and HF worsening are the strongest predictors for depression development after ICD/CRT-D implantation. Depression is a strong, independent risk factor of poor outcomes in HF population. Funding Acknowledgement: Type of funding source: None